Selling the ivory tower and regional development: Technology transfer offices as mediators of university-industry linkages - Christian Reiner (University of Salzburg, Department of Social Sciences and Economics, 2010)
This article focuses on the role of Technology Transfer Offices (TTOs) in regional development in three Austrian regions that represent different types of regional economies. TTOs can be defined as 'bridging institutions' between academia and business. The value added by this approach emerges due to empirical results demonstrating that the variety of TTO functions and their respective spatial-profile of activities depend heavily on the regional context. Regional economic structure and regional policy systematically shape the spatial profile of TTO activities. The distinction between active and passive TTOs emerged as an important one regarding their potential regional economic development impact. While passive TTOs merely facilitate already existing contacts of the academic staff, active TTOs generate new university-industry linkages. These additionally created contacts are heavily biased towards the regional level. Intellectual property rights (IPR)-related TTO activities show a rather weak regional impact. This might prove problematic for policy makers that foster the patent-oriented commercialization of knowledge as a means to intensify knowledge spillovers from the universities to regional or national firms.
Keywords: I23; I28; O34; O33; R11; R58; 330; Universities; technology transfer offices; regional innovation systems; regional policy; Austria